Short-term plant legacy alters the resistance and resilience of soil microbial communities exposed to heat disturbance in a Mediterranean calcareous soil. (January 2020) - de Oliveira, Ana Beatriz; Cantarel, Amélie A.M.; Seiller, Marie; Florio, Alessandro; Bérard, Annette; Hinsinger, Philippe; Le Cadre, Edith
Highlights: Short-term plant legacy impacts resistance and resilience of C and N soil functions. Intercropping species confer different plant legacies compared to sole crops. Plant legacy has to be investigated to mitigate heat waves in Mediterranean soil. Abstract: Plant legacy is a concept representing the effects exerted by plants on soil once they are no longer growing. We hypothesized that plant species and mixture (intercropping) would induce different short-term legacy effects impacting carbon and nitrogen-related soil microbial activities and resistance and resilience after a heat disturbance. A microcosm experiment was conducted using a calcareous Mediterranean soil conditioned by a complete vegetative cycle in a greenhouse with four planting modalities (W = monoculture of Wheat ( Triticum aestivum L.); L = monoculture of white Lupin ( Lupinus albus L.); WL = both species intercropped; U = unplanted soil). Half of microcosms were incubated at 28 °C (C = control conditions) whereas the remaining half were exposed at 48 °C for 2 days (S = stress conditions), with an immediately return to control conditions. Microcosms were destructively sampled at 2, 7, 16 and 28 days (T2, T7, T16, T28) after the end of the heat disturbance and the following soil measurements were performed: Basal Respiration (BR), Substrate-Induced Respiration (SIR), Nitrification Enzyme Activity (NEA) and N mineral concentrations. Our results demonstrated that monocultures and intercropping promoted different legacy effects under control conditions especially for SIR. WL soils presented lower values of SIR than L and higher than W soils. For SIR, W and WL soils conferred greater resistance to the heat stress, whereas L and WL soils conferred higher resilience at T28. For NEA, no differences between soils were observed for resistance to heat stress, but at T16, soils having WL legacy were more resilient than L soils, but comparable to those having W legacy. Our results highlight that a short-term legacy effect is measurable but greatly differs between C- and N-related microbial activities. We estimated that intercropping had modified ability of soil microorganisms to face heat stress, suggesting that plant legacy effect has to be considered to mitigate extreme climatic events in Mediterranean soils.